Multimodal Discourse Analysis on Geopark Kebumen Website - Salsabila, Verosiana Vira; Sari, Eka Dyah Puspita; Solikhah, Ika Maratus (Gadjah Mada Journal of Tourism Studies, 2025)
Sustainable tourism is the most suitable concept to protect Indonesian realms and cultural diversity besides the tourist destination’s development. One of the websites that displays sustainable tourism is geoparkkebumen.id. This research aims to describe the verbal and visual modes on the homepage display of the website. It is qualitative research with purposive sampling in getting the data. The data is analyzed using Kress & van Leeuwen’s, Lamb’s, and Peirce’s theories. The result of the analysis shows that the website uses some figurative language as the verbal modes. Assonance appears as the most used figurative language. It is chosen to make the website more persuasive and memorable for the readers. Rhetorical question does not appear on the website. The website avoids using it to maintain clarity, objectivity, and an authoritative tone, ensuring readers get straightforward information. The analysis of visual mode reveals that images on the website contain high angle, eye-level angle, and oblique angle. These angles enhance visual storytelling, complementing verbal descriptions to engage readers effectively. Future researchers can involve different actual issues to enrich multimodal discourse analysis.